Neuroimaging in Kabuki syndrome and another KMT2D‐related disorder. Issue 12 (9th August 2021) - Stadelmaier, Rachel T.; Kenna, Margaret A.; Barrett, Devon; Mullen, Thomas E.; Bodamer, Olaf; Agrawal, Pankaj B.; Robson, Caroline D.; Wojcik, Monica H.
Abstract: Recognition of distinct phenotypic features is an important component of genetic diagnosis. Although CHARGE syndrome, Kabuki syndrome, and a recently delineated KMT2D Ex 38/39 allelic disorder exhibit significant overlap, differences on neuroimaging may help distinguish these conditions and guide genetic testing and variant interpretation. We present an infant clinically diagnosed with CHARGE syndrome but subsequently found to have a de novo missense variant in exon 38 of KMT2D, the gene implicated in both Kabuki syndrome and a distinct KMT2D allelic disorder. We compare her brain and inner ear morphology to a retrospective cohort of 21 patients with classic Kabuki syndrome and to typical CHARGE syndrome findings described in the literature. Thirteen of the 21 Kabuki syndrome patients had temporal bone imaging (5/13 CT, 12/13 MRI) and/or brain MRI (12/13) which revealed findings distinct from both CHARGE syndrome and the KMT2D allelic disorder. Our findings further elucidate the spectrum of inner ear dysmorphology distinguishing Kabuki syndrome and the KMT2D allelic disorder from CHARGE syndrome, suggesting that these three disorders may be differentiated at least in part by their inner ear anomalies.